Real-Time Analysis on Drug-Antibody Ratio of Antibody-Drug Conjugates for Synthesis, Process Optimization, and Quality Control - Yubo Tang (Nature Portfolio, 2017)
Abstract Drug-antibody ratio (DAR) of antibody-drug conjugates (ADCs) is important for their therapeutic efficacy and pharmacokinetics, therefore control on DAR in synthesis process is a key for ADC quality control. Although various analytical methods were reported, the real-time monitoring on DAR is still a challenge because time-consuming sample preparation is usually needed during the analysis. Antibody deglycosylation of ADC simplifies DAR measurement, however long-time PNGaseF digestion for deglycosylation hampers the real-time detection. Here, we report a rapid DAR analysis within 15 min by robust deglycosylation treatment and LC-MS detection that enables real-time DAR monitoring for optimization on ADC synthetic process. With this approach, we were able to screen suitable conjugation conditions efficiently and afford the ADCs with expected DARs. To the best of our knowledge, this is the first report on real-time DAR analysis of ADCs for conjugation optimization and quality control, compatible with random lysine-linked ADCs, glycosite-specific ADCs, and the complicated dual-payload ADCs.